New PWM switching techniques for an optimum cascade 3/3 NPC inverter operation. - Sơn, Nguyễn Hoài; Nhờ, Nguyễn Văn; Dương, Lê Văn (Journal of Computer Science and Cybernetics, 2012)
Many researches and industrial applications have demonstrated unique and attractive features of multilevel inverters including high power quality, good harmonic performance, good electromagnetic compatibility, and low switching losses. In recent years, several new cascaded multilevel inverters are developed for increasing drive performance, reducing the drive complexity and losses. Among those, through a series connection of two three-level NPC inverters, a cascade-3/3 inverter was created with enormous advantages. This paper presents new carrier-based PWM modulations to control this dual topology for optimum operation. In terms of power sources, this cascaded inverter is operated either from isolated dc sources (series power cells) or from a single dc source. Computer simulation and experimental validation are shown to verify the proposed techniques.